Synthetic peptides as valuable and versatile tools for research: our 20 year journey in Chile - Constanza Cárdenas; Paula Santana; Claudio Álvarez; Luis Mercado; Sergio Marshall; Fernando Albericio; Fanny Guzmán (Exploration of Drug Science)
According to the International Union of Pure and Applied Chemistry (IUPAC), peptides are small proteins with a size between 2 and 50 amino acids residues. They are ubiquitous across the evolutionary scale, fulfilling a wide variety of functions, from immune system effectors in simple organisms to signaling or neuromodulating agents in high vertebrates. Following nature’s example, peptides have emerged as alternatives in various fields. One particularly relevant area is in drug discovery, offering alternatives to face the emergence of antibiotic-resistant microorganisms. Peptides are also prevalent in other sectors, such as the food industry, where they serve as food additives to enhance nutritional characteristics or aid in food preservation. Moreover, peptides are increasingly being utilized in cosmetics. Additionally, peptides serve as valuable tools in both basic and applied research, facilitating the exploration of specific activity mechanisms and the verification of particular activities, among various other applications. Despite certain limitations and disadvantages compared to other bioactive molecules, peptides remain a focal point of interest in research, as well as in applied and developmental fields, due to their versatility. In this report, we provide an overview of the extensive application landscape of synthetic peptides, presenting examples developed in-house across different areas which include a summary of the methodologies and results obtained.